Hormonal and Laboratory Profile of Polycystic Ovarian Syndrome (Pcos) Women Visiting Fertility Center in Indonesia - Sundari, Ayu Mulia; Wulandari, Tri Aprilliana; Prakoso, Nurul Muhammad; Dwiranti, Astari; Abinawanto; Boediono, Arief; Funahashi, Hiroaki; Bowolaksono, Anom (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Our study aims to scrutinize the hormonal and laboratory profile of women with PCOS visiting a fertility center in Indonesia. A computerized database of 120 PCOS women and 120 controls was retrospectively reviewed and analyzed. According to analysis, the concentration of AMH and basal LH were significantly more elevated in the PCOS group than in the control group (6.77 vs. 2.05, P<0.001; and 6.8 vs. 5.3, P<0.001, respectively). The level of basal FSH was significantly lower in the PCOS group (5.83 vs. 7.86; P<0.001). After an IVF cycle, PCOS women had significantly higher retrieved oocytes and mature oocytes compared to controls (18 vs. 8, P<0.001; 12 vs. 6, P<0.001). The number of fertilizations, cleavages, and top-quality cleavages were also higher in the PCOS group than in the control group (10 vs. 4, P<0.001; 10 vs. 4, P<0.001; 4 vs. 2, P<0.001). At the blastocyst stage, patients with PCOS had a higher number of blastocysts and top-quality blastocysts than control (9 vs. 4, P<0.001); 4 vs. 1, P<0.01). However, the clinical pregnancy was significantly higher in the control group than in the PCOS group (52.6% vs. 16.7%; P = 0.045).